Feasibility study of a wellness intervention for caregivers of patients undergoing hematopoietic stem cell transplantation: The Ready to CARE Intervention. (March 2021) - Morency, Jamme L; Caldon, Kate L; Root, Lynn; Hayes, Christi A; Brighton, Susan; Lyons, Kathleen Doyle
Introduction: Caregivers of patients undergoing hematopoietic stem cell transplantation need encouragement to maintain their own wellbeing. This feasibility study explored a six-session wellness intervention for caregivers entitled Ready to CARE (Connect, Actively Relax, and Exercise). Method: This study used a single-arm pre–post design to explore the feasibility and acceptability of the intervention and study procedures. The individual, participant-directed intervention was initiated at hospitalization for stem cell reinfusion. Caregivers completed telephone surveys on four occasions and engaged in one semi-structured interview to share their perceptions of the intervention. Results: Twenty participants enrolled and completed the baseline survey, with 50%, 90%, and 80% completing the subsequent three surveys, respectively. Seventy-four percent completed all six sessions of the intervention. Caregivers most often used the sessions to set goals related to physical activity (36%), stress management (14%), sleep (13%), and caregiving tasks (11%). Caregivers reported appreciation of the intervention's focus on supporting caregivers, taking action with goal-setting, and allowing caregivers to determine the focus of the goals. Scheduling the sessions was the most problematic aspect of the intervention. Conclusion: While caregivers were open to a wellness intervention, a high degree of flexibility and tailoring is needed to engage and support busy caregivers. Clinical Trial Registration: NCT03210727